"With tramadol, I ride like a Jaguar": a qualitative study of motivations for non-medical purpose tramadol use among commercial vehicle operators in Kumasi, Ghana - Prince Peprah; Williams Agyemang-Duah; Emmanuel Appiah-Brempong; Adjei Gyimah Akwasi; Anthony Kwame Morgan (BMC, 2020)
Abstract Background The misuse of tramadol has become a major aspect of the wider substance use challenge in recent years and is evolving into a health crisis at an alarming rate. However, literature on motivations for non-medical purpose tramadol use among commercial vehicle operators remains inadequate. The aim of this study was to document the motivations for non-medical purposes tramadol use in Kumasi. Such an understanding could inform policy direction to regulate non-medical purposes tramadol use in Ghana. Methods We conducted this exploratory qualitative study with 23 purposively selected commercial vehicle drivers (15) and assistants (8) in Kumasi, Ghana. Data for the study were collected through in-depth face-to-face interviews between June 2018 and March 2019. Using a thematic analytical approach, the interviews were coded and analysed. Results Multiple motivations for non-medical purposes tramadol use were found including those related to: (1) sexual; (2) psychological; (3) physical; and (4) economic factors. Participants also reported three main inter-linking categories of perceived tramadol adverse effects: (1) physical; (2) psychological; and (3) social effects. Although participants indicated no plans for stopping their non-medical use of tramadol any time soon, strong willingness was voiced for supporting officials in finding and dealing with non-medical purpose tramadol sellers. Conclusion Non-medical purposes tramadol use was associated with a confluence of factors, ranging from enhanced sexual performance to economic reasons. Based on the findings of the study and the dependence and addictive potentials of tramadol, there is the need for psychoeducational programmes for persons who misuse tramadol and enhancement of operational capacities of regulatory agencies.